Interpolation of compact non-linear operators - Bento AJG (Journal of Inequalities and Applications, 2000)
Let and be two Banach couples and let be a continuous map such that is a Lipschitz compact operator and is a Lipschitz operator. We prove that if is also compact or is continuously embedded in or is continuously embedded in , then is also a compact operator when and . We also investigate the behaviour of the measure of non-compactness under real interpolation and obtain best possible compactness results of Lions–Peetre type for non-linear operators. A two-sided compactness result for linear operators is also obtained for an arbitrary interpolation method when an approximation hypothesis on the Banach couple is imposed.